HUBUNGAN KONSEP DIRI DENGAN PENERIMAANPERUBAHAN FISIK MASA PUBERTAS PADA SISWI DI SMPN I TEMBILAHAN - Yoneta Oktaviani (STIKES HUSADA GEMILANG, 2019)
Adolescence is known as one of the periods in the span of human life that has several unique features. This uniqueness comes from the adolescence as a transitional period between childhood and adolescence or puberty. During this period, the attitudes of individual meet several changes both physical and psychological. Young women seem to dislike physical changes when they are teenagers, especially regarding the increase in body fat. This physical change can cause young women to feel shy and close themselves to the environment. This research is analytical, with a population of 166 people and sample as 117 people. Data analysis uses chi-square statistical test. The results reveal that young women in puberty at SMPN 1 Tembilahan whose concept was in good category were 53% and 47% of themselves were not good. Young women in puberty have a positive acceptance of physical changes as 47%, and negative acceptance of physical changes as 53%. Based on the results, it is gained that the value of p=0.018, it can be concluded that there is a significant relationship between self-concept and acceptance of physical changes in puberty. Therefore, it is expected that midwifery services pay more attention to health education in adolescents about changes that occur during puberty to prepare them for puberty.